Strategi Pemerintah Daerah Kabupaten Nganjuk dalam Melestarikan Kawasan Cagar Budaya sebagai Implementasi Konsep Hifzh al-Turats (Menjaga Warisan) dalam Islam - Samsul Munir; Rona Merita (Universitas Pangeran Diponegoro Nganjuk, 2025)
This study examines the conservation strategy employed by the Nganjuk Regency Regional Government in preserving its Cultural Heritage Areas, analyzed through the lens of the Islamic concept of Hifzh al-Turats (Preservation of Heritage). Cultural heritage is not merely a historical and archaeological asset but also an integral part of civilizational identity that must be protected. This research employs a qualitative descriptive method with data collection techniques through interviews, observation, and documentary studies. The findings indicate that the Nganjuk government's strategy is multidimensional, encompassing the physical restoration and maintenance of sites, strict regulatory enforcement against damage, and active community engagement through educational and cultural programs. This approach aligns profoundly with the principles of Hifzh al-Turats, which emphasizes the obligation of every generation to protect and transmit its cultural, scientific, and historical legacy to the future. The implementation of this strategy demonstrates how local wisdom and religious values can synergize with government policy to create effective and sustainable conservation efforts. This research concludes that the Nganjuk government’s model offers a valuable framework for other regions, illustrating that cultural preservation is both a civic duty and a manifestation of religious teachings aimed at maintaining the continuity of civilization and strengthening national identity.